KOMPETENSI PEDAGOGIK MAHASISWA PROGRAM STUDI PENDIDIKAN GURU SEKOLAH DASAR - Huda, Muhammad Nailul; Marhadi, Hendri; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is a survey research about Competence of Pedagogic Students of Primary School Teacher Education Program University of Riau. The purpose of this research is to know and describe University of Riau of Riau University. This research was conducted in Teacher Education Program of Elementary School Faculty of Teacher Training and Education University of Riau on July 2017 until August 2017. The sample of this research is student of Generation 2014 with amount of 76 respondents. Data collection techniques used is a written test technique with the instrument of this study is an objective matter about teacher pedagogic competence with four alternative answers with the number 49 questions. The analysis technique used in this research is descriptive analysis technique. The results indicate that students' pedagogical competencies are included in the